Interaction and Interpersonal Communication of Vendors: Symbolic Interaction Study of P&D Traders and Buyers at Pasar Raya Kota Solok - Diego Diego; Yayuk Lestari; Novi Elian; Robby Mandala Putra (Penerbit Jurnal Indonesia, 2024)
This study to examinate of traders' verbal and nonverbal communication at Pasar Raya Kota Solok, and their utilization of verbal and nonverbal symbols in interpersonal interactions within the realm of trade transactions. This research uses a qualitative approach by collecting data through participatory observation and interviews with traders and buyers. The results of the study show that verbal communication between sellers and buyers involves the use of greetings, bargaining, and questions about products. In addition, non-verbal communication consisting of body language, facial expressions and body movements also plays an important role in the interaction between traders and buyers. Using appropriate non-verbal communication, such as smiles, eye contact and friendly gestures, can help build good rapport and increase buyer loyalty to merchants. This study also emphasizes the importance of symbolic interaction theory in understanding social interaction in traditional markets. Social interactions between merchants and buyers involve the use of dynamic symbols, such as language and body movements, to communicate and understand each other's needs and wants. This theory shows that traders' thoughts and self-construction are inseparable from the social context and interactions with society. Traders use symbols and social interactions to convey messages, create meaning, and develop self- images that conform to the norms and values in society. Communication and the formation of social meaning in this interaction have an important role in shaping the self-concept of traders as sellers who are competent and care about customers.